Effects of Andrographis paniculata Leaf Extract on C-Reactive Protein and Serum Ferritin in Lipopolysaccharide-Induced Sepsis Model Rat - Rezya Salsabela; Nyoman Suci Widyastiti; Dwi Retnoningrum; Ariosta Ariosta; Neni Susilaningsih (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: C-reactive protein (CRP) and ferritin are acute-phase reactants that have demonstrated association with the severity of a variety of inflammation-mediated illnesses, including infection and sepsis. Sambiloto (Andrographis paniculata) leaf is traditionally used as an anti-inflammation and anti-bacterial herb. Sambiloto leaf extract possesses anti-inflammatory, antiallergenic, immuno-stimulatory, antiviral, and antioxidant activitiesObjective: To evaluate the effect of Sambiloto leaf extract (Andrographis paniculata) on inflammation biomarker (CRP and serum ferritin) in a rat model of sepsis-induced by lipopolysaccharide (LPS).Methods: This research was a true experimental study with a post-test-only control group design. Twenty five male Wistar rats were randomly divided into 5 groups consisting of a healthy control (HC), Negative control (NC), Treatment 1 (T1) Sambiloto 200mg/kgBW, T2 Sambiloto 400mg/kgBW, T3 Sambiloto 500mg/kgBW). Sambiloto leaf extract was given on days 8-21 and LPS 5mg/kgBW was injected intraperitoneal on day 22. On the 25th day, blood was drawn and CRP and serum ferritin levels were analyzed using ELISA method. The data were analyzed using One-Way ANOVA and Kruskal Wallis test.Results: The mean CRP levels of HC, NC, T1, T2,T3 were 7.72 ± 2.53; 8.12 ± 1.08; 5.22 ± 1.71; 6.40 ± 1.19; 5.14 ± 1.37 ng/dl respectively. The mean serum ferritin level of HC, NC, T1, T2, T3 were 293.60 ± 66.53; 601.20 ± 100.17; 433.40 ± 194.65; 331.60 ± 75.97; 318.00 ± 69.64 ng/dl respectively. There were differences in CRP levels in groups T1(p=0.012) and T3(p=0.010), serum ferritin levels in groups T2(p=0.014) and T3(p=0.008) to the control group.Conclusion: Sambiloto (Andrographis paniculata) leaf extract has anti-inflammatory effects in the rat model of sepsis.